A Novel Approach for Water‐Insoluble Ammonium Polyphosphate Crystal Form II and V. Issue 36 (27th September 2018) - Pan, Detao; Wu, Yanyang; Wu, Bin; Kui, Chen; Ji, Lijun; Zhu, Jiawen
Abstract: Water‐insoluble ammonium polyphosphates (n‐APPs) are very important intumescent flame retardants for polymer materials. In this study, a novel preparation for n‐APPs has been proposed by using diammonium hydrogen phosphate (DAP) and dicyandiamide (DICY). In comparison to the reported processes, the synthesis in this paper has the following advantages such as more economic and energy‐saving, mild reaction conditions with less gas release. The preparation can be divided into two steps, the reaction and the crystallization. The reaction pathway has been studied by FTIR techniques. Relatively pure crystal form II and crystal form V were obtained under their specific conditions. Finally, TG analysis has shown that the products have high thermal stability; the linear structure of the n‐APPs products has been confirmed by the liquid NMR techniques; the element and solubility analysis have been conducted and they conform to the requirements of the HG/T 2770–2008 industrial standard. Abstract : In this paper, we proposed the reaction pathway of diammonium hydrogen phosphate and dicyandiamide for the preparation of ammonium polyphosphate and it has been confirmed by FTIR method. DICY hydrolyzed by heat treatment under the experimental conditions, and guanidine phosphates were formed, followed by dehydrating of –P‐OH groups in guanidine phosphates. Two relatively pure crystal form of water‐insoluble ammonium polyphosphate were obtained by control the crystalline temperature.